2018
DOI: 10.1159/000492292
|View full text |Cite
|
Sign up to set email alerts
|

NR4A1 Promotes Diabetic Nephropathy by Activating Mff-Mediated Mitochondrial Fission and Suppressing Parkin-Mediated Mitophagy

Abstract: Background/Aims: Disrupted mitochondrial dynamics, including excessive mitochondrial fission and mitophagy arrest, has been identified as a pathogenic factor in diabetic nephropathy (DN), although the upstream regulatory signal for mitochondrial fission activation and mitophagy arrest in the setting of DN remains unknown. Methods: Wild-type (WT) mice and NR4A1 knockout (NR4A1-KO) mice were used to establish a DN model. Mitochondrial fission and mitophagy were evaluated by western blotting and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 74 publications
3
52
2
Order By: Relevance
“…Consistently, the basal levels of Nr4a1, body weight, FBG, TG, TC, LDL-C, and HDL-C were higher in T2DM patients [30]. As recently reported, Nr4a1 was actually activated by chronic hyperglycemia, and higher Nr4a1 expression has strong links with glucose metabolism disorder, renal insufficiency, renal hypertrophy, and fibrosis, but Nr4a1 knockdown reduced diabetic renal damage [20]. Therefore, our results support that Nr4a1 depletion is beneficial for T2DM treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistently, the basal levels of Nr4a1, body weight, FBG, TG, TC, LDL-C, and HDL-C were higher in T2DM patients [30]. As recently reported, Nr4a1 was actually activated by chronic hyperglycemia, and higher Nr4a1 expression has strong links with glucose metabolism disorder, renal insufficiency, renal hypertrophy, and fibrosis, but Nr4a1 knockdown reduced diabetic renal damage [20]. Therefore, our results support that Nr4a1 depletion is beneficial for T2DM treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The volume of adipocytes and the size of lipid droplets in WATs increased notably (both p<0.05, Figure 1D, 1E), inferring the successful establishment of the T2DM rat model. According to the literature, Nr4a1 is a newly-discovered malignant factor in diabetic renal damage [20]. Therefore, we speculated that Nr4a1 would have an effect on T2DM rats.…”
Section: Nr4a1 Is Upregulated In Wats Of T2dm Ratsmentioning
confidence: 94%
“…Previous reports have argued that the protective endothelial effect of Sirt1 is closely associated with the regulation of mitochondrial functions by limiting mitochondrial DNA damage and preventing the activation of mitochondrial damaging MMP-9 (11,43,44). Furthermore, mitochondrial dysfunction caused by mitochondrial fission is reported to be involved in the development of diabetic nephropathy (7,45) and diabetic cardiomyopathy (46). These results indicate the involvement of mitochondrial fission in the development of HG-induced endothelial injury and diabetic vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that mitochondrial fission serves an important role in mitochondrial homeostasis (5,6). Furthermore, mitochondrial fission factor (Mff)-mediated mitochondrial fission is considered to be an important facet of diabetic complications (7). Excessive mitochondrial fission leads to cellular energy metabolism disorders, ROS bursts, increased mitochondrial permeability transition pore (mPTP) opening volumes and the activation of mitochondrial-dependent cell apoptotic procedures in response to HG treatment (8).…”
Section: Introductionmentioning
confidence: 99%
“…Because mitochondria are the key sites of glucose metabolism, we speculate that a precise investigation of mitophagy will shed light on the role of autophagy in type 2 diabetes osteoporosis. Sheng et al reported the positive effect of mitophagy on hyperglycemia-mediated mitochondrial damage in diabetic nephropathy 17 . In contrast, Wang et al found that attenuation of mitophagy may reduce mitochondrial loss and increase mitochondrial biogenesis in the skeletal muscles of diabetic rats 18 , but the effect of mitophagy on type 2 diabetes osteoporosis remains unclear.…”
mentioning
confidence: 99%